Answer:
(1/2,4)
Step-by-step explanation:
First, determine y in first equation: 2x+y=5 or y=5-2x
replace value of y determined in first equation (5-2x) into 2nd equation
4x-3(5-2x)=-10
4x-15+6x=10
10x=5
x=1/2
put value of x into either equation to solve for y so
2(1/2)+y=5
1+y=5
y=4
answer: x=1/2, y=4
check answer by substituting x and y into either equation:
4x-3y=-10
4(1/2)-3(4)=-10
2-12=-10
-10=-10
or
2x+y=5
2(1/2)+4=5
1+4=5
5=5
Answer:
Thanks for the point!
Step-by-step explanation:
Have a great day
Answer:
Its the 3rd answer :)
<em>x = 26.94</em>
Step-by-step explanation:
<h2><em>This is because 25.5 + 1.44 = 26.94 :) (inverse operations ;))</em></h2>
<em />
Answer:-8x^2-6x+36xy^2+27y^2
Step-by-step explanation:
using the FOIL method
Answer:15/17
Step-by-step explanation: cos = adjacent/hypotenuse